Charge characteristics of the MOS structures with oxide films containing Si nanocrystals - Begun, E.V.; Bratus’, O.L.; Evtukh, A.A.; Kaganovich, E.B.; Manoilov, E.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The processes of charge accumulation in the MOS structures with SiO₂ films containing Si nanocrystals are investigated, depending on the conditions of their formation by pulsed laser deposition. High-frequency capacity-voltage characteristics of structures with the different thicknesses of films, sizes of Si nanocrystals, and their densities in the case of doping the films with gold and without it are measured. It is shown that the positive and negative charges are built-in, respectively, in the undoped films and those doped with gold. At the record of C-V curves, the accumulation of a positive charge is observed. The value of accumulated charge is higher in thin films and in the films doped with gold. The obtained results testify the possibility of the use of pulsed laser deposition for creation of memory structures based on the charge capture by Si nanocrystals.